Analysis Of Environmental Management Accounting Application In The Manufacturing Industry In Makassar City (Empirical Study On Cake Companies) - Nurhikmah Syahrir; Masdar Mas’ud; Syamsuri Rahim (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This research was motivated by the existence of several problems related to the rapid growth of the manufacturing industry in Makassar City and inevitably led to the encroachment of the existing waste figures. In addition, the handling of waste generated by the manufacturing industry in particular still needs to be analyzed regarding its reporting and treatment. This study aims to determine how the application of environmental management accounting in the manufacturing industry in the city of Makassar, especially in the Cake company. This research was carried out for two months, namely in January-February 2021, taking place in 4 cake industries in Makassar City, namely, Sari Roti, JCO Donnuts and Coffe, Chocolicious, and Boluta' Makassar. To process the data, the author uses a qualitative descriptive method. The results show that: 1) There are three industries that already know and understand environmental management accounting, while 1 industry does not understand at all. 2) But of the three industries that understand management accounting, only 2 apply it in the form of reports in making management decisions for the next steps to be taken, 3) Industries that have not implemented it are caused by the lack of knowledge about environmental management accounting in Makassar City 4) The output of Environmental Management Accounting produced by the industry that has implemented it is by holding CSR activities and various forms of attention to the environment.